KASULI “Kafe Susu Tuli” sebagai inovasi wadah habilitasi dan pemberdayaan ekonomi penyandang Tuli di Yogyakarta - Hastuti, Wanodya Prabaning Widhi; Az-Zahroh, Safura; Hastuti, Novia Rahma; Dinnajah, Nur Rifda; Alawi, Uzwa As'ari; Rafikayati, Ana (Literal: Disability Studies Journal, 2025)
Equal employment opportunities for persons with disabilities, particularly the Deaf community, remain a persistent challenge in Indonesia. Social stigma and lack of access to inclusive work environments often hinder their ability to fully develop their potential. This study aims to explore how KASULI (Kafe Susu Tuli), a social enterprise based in Yogyakarta, promotes economic independence while raising public awareness on the importance of inclusion. Employing a qualitative approach with a descriptive method, data were collected through direct interviews with the founder of KASULI, a Deaf individual. The findings reveal that KASULI functions not only as a business enterprise but also as a space for education and social interaction between the general public and the Deaf community. This initiative has proven effective in reducing stigma, boosting self-confidence among Deaf individuals, and inspiring the development of similar inclusive businesses in other regions. These findings emphasize the importance of community support and awareness in fostering a disability-inclusive entrepreneurial ecosystem.